Communication technology security and information security in enterprises of engineering construction - Klimek, Michał (Management and Administration Journal, 2023)
The aim of the article is to present aspects related to the teleinformatic safety and use of the Information Security Management System in engineering construction enterprises. This system is part of the Integrated Management System in these companies. It is one of the most important elements of the Integrated Management System. It helps in building the position of construction companies at the domestic and international level, and supports the management of confidential information, as well as the smooth and secure operation of applied technology and data processing.